2022
DOI: 10.1186/s12916-022-02369-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating agreement between bodies of evidence from randomized controlled trials and cohort studies in medical research: a meta-epidemiological study

Abstract: Background Randomized controlled trials (RCTs) and cohort studies are the most common study design types used to assess the treatment effects of medical interventions. To evaluate the agreement of effect estimates between bodies of evidence (BoE) from randomized controlled trials (RCTs) and cohort studies and to identify factors associated with disagreement. Methods Systematic reviews were published in the 13 medical journals with the highest impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 112 publications
(110 reference statements)
2
25
0
Order By: Relevance
“…Overall, 64 systematic reviews of RCTs and cohort studies were included [ 13 76 ]. Of the identified 129 outcome pairs, 118 from 59 systematic reviews were included in the present pooling scenario and re-analyzed (Additional file 1 : Table S2-S3) [ 7 , 13 76 ] (109 dichotomous and nine continuous outcomes) (Additional file 1 : Figs. S1-118).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 64 systematic reviews of RCTs and cohort studies were included [ 13 76 ]. Of the identified 129 outcome pairs, 118 from 59 systematic reviews were included in the present pooling scenario and re-analyzed (Additional file 1 : Table S2-S3) [ 7 , 13 76 ] (109 dichotomous and nine continuous outcomes) (Additional file 1 : Figs. S1-118).…”
Section: Resultsmentioning
confidence: 99%
“…The sample of this empirical study was based on a large meta-epidemiological study [ 7 ], which was planned, written, and reported in adherence to current guidance for meta-epidemiological methodology research [ 8 ]. Eligibility criteria (PI/ECO: patient/population, intervention/exposure, comparator, and outcome) are reported in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations